Volumetric and spatial changes in brain metastases during stereotactic radiosurgery: a case for off-line adaptive planning - Menekse Turna; Hale Başak Çağlar (Clinical and Translational Radiation Oncology)
Stereotactic radiosurgery is a widely used treatment modality for brain metastases, particularly in cases with a limited number and volume of lesions. While adaptive strategies have gained prominence in the stereotactic treatment of extracranial, their application in intracranial SRS remains largely unexplored. This case study presents a 45-year-old female with multiple brain metastases and significant perilesional edema, treated with fractionated stereotactic radiotherapy. Due to tumor displacement during the treatment course, adaptive SRS was implemented after the third fraction, utilizing an updated MRI scan to account for changes in tumor volume and midline shift. The total GTV decreased by 34.2 %, and five lesions were found to be partially outside the prescribed treatment target. Based on this MRI, an offline adaptive SRS plan was generated, and the remaining two fractions were delivered according to the updated plan. This case underscores the potential for significant changes in target volume and spatial displacement during FSRT in patients with brain metastases exhibiting extensive edema and emphasizes the importance of mid-treatment imaging and the potential role of offline adaptive SRS strategies in managing intracranial tumors.